Student Difficulties on Reading Comprehension in Explanation Text at Eleventh Grade Students of MAN 1 Makassar - Achmad Chrisbianto Sachran; Munir Munir; Nur Aeni (Journal of Excellence in English Language Education, 2022)
The activity of reading is very important because with reading students get new words in learning English, especially in writing, speaking, and listening. And also Reading skills teach students how to pronounce the words of the sentence in the text. With reading, students can understand the existing conditions and situations. The student also will do some activities by reading in every place, reading some words, and sentences or passages. By reading, students will get the information, knowledge, and idea. Reading is also having important in education, especially in teaching and learning processes. Nowadays teachers usually teach reading only gives the clue or material point related to the material.